2011
DOI: 10.1063/1.3665185
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical stability of ordered droplet packings in microfluidic channels

Abstract: The mechanical response and stability of one and two-row packing of monodisperse emulsion droplets are studied in quasi 2d microchannels under longitudinal compression. Depending on the choice of parameter, a considered droplet arrangement is either transformed continuously into another packing under longitudinal compression or becomes mechanically unstable and segregates into domains of higher and lower packing fraction. Our experimental results are compared to analytical calculations for 2d-droplet arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A large impact of the volume fraction on the appearance and stability of certain droplet and particle packings in confinement has been reported in a number of microfluidic experiments [11][12][13][14][15]. Transitions between single-row, two-row, and threerow packings of monodisperse emulsion droplets in tapered channels have been described in detail by Surenjav et al in Ref.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A large impact of the volume fraction on the appearance and stability of certain droplet and particle packings in confinement has been reported in a number of microfluidic experiments [11][12][13][14][15]. Transitions between single-row, two-row, and threerow packings of monodisperse emulsion droplets in tapered channels have been described in detail by Surenjav et al in Ref.…”
Section: Introductionmentioning
confidence: 86%
“…Above a certain volume fraction, however, the transitions in the widening segment occur at a larger channel width than the inverse transition, i.e., an increasing hysteresis of the transitions is observed that eventually reaches the strong hysteresis observed in dry emulsions [14]. Using plugs of a fluorinated oil that is immiscible to both the droplet and the continuous phases allows one to compress a stack of droplets in a flat microfluidic channel and to study packing transitions [15]. Besides transitions between congruent droplet arrangements, a longitudinal separation into packings with high and low packing fractions is observed in a certain range of confinement and volume fraction [15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…41 Alternatively, the foam or emulsion could be compressed such that the effective length of the channel decreases by forcing the excess liquid out of the channel and causing the inclusions to deform and rearrange as necessary. 19 The bubble or droplet volume can also be controlled by the introduction of an automated system that would allow for a greater accessible range of bubble and droplet sizes, such as one that incorporates external valves. 42 …”
Section: Discussionmentioning
confidence: 99%
“…The packing transition from two to three dimensions was observed by Pieranski et al and characterized as a function of separation distance between the two confining surfaces. 18 A change in the total length of the channel will also induce a change in the structure, as described in compression studies performed by Fleury et al 19 In three-dimensional space, Hatch et al…”
Section: Introductionmentioning
confidence: 99%